2018
DOI: 10.3389/fphys.2018.01468
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Exercise Mode on Post-exercise Arterial Stiffness and Pressure Wave Measures in Healthy Adult Males

Abstract: Background: Exercise mode has been reported to be an important determinant of arterial stiffness and wave reflection changes following a brief bout of exercise with inconsistent results to date. This study examined the impact of exercise mode on arterial stiffness and pressure wave measures following acute aerobic exercise (AER), resistance exercise (RES), and a control (CON) condition with no exercise.Methods: In a randomized, cross-over, repeated measures design, 21 healthy adult males (26.7 ± 7.2 years) und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 68 publications
(115 reference statements)
5
19
1
Order By: Relevance
“…Reductions were not detected after RE, but it should be noted that there were no increases either, as previously reported in normotensive individuals 12 , 22 , 26 , 44 . While reductions in AIx after acute AE have been previously demonstrated 10 , 17 , 45 , data regarding RE are few and inconsistent 12 , 26 , 46 . A recent meta-analysis 4 including trials mostly developed with healthy individuals reported significant reductions in AIx following acute AE but not RE, while increases in AIx75 were detected after both AE and RE.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Reductions were not detected after RE, but it should be noted that there were no increases either, as previously reported in normotensive individuals 12 , 22 , 26 , 44 . While reductions in AIx after acute AE have been previously demonstrated 10 , 17 , 45 , data regarding RE are few and inconsistent 12 , 26 , 46 . A recent meta-analysis 4 including trials mostly developed with healthy individuals reported significant reductions in AIx following acute AE but not RE, while increases in AIx75 were detected after both AE and RE.…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, shear stress patterns affecting vasoconstriction seem to depend on exercise mode 25 , 49 . Most trials reporting a reduction in AIx following AE linked this finding to increased peripheral vasodilation, rather than to a reduced sympathetic vasoconstriction 9 , 10 , 12 , 45 . The few studies that observed reductions in PWR after acute RE, also suggested that this would be secondary to changes in the transit time of the reflected wave 15 due to peripheral vasodilation mediated by local metabolite accumulation 10 , 47 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations